Blood‐based detection of RAS mutations to guide anti‐EGFR therapy in colorectal cancer patients: concordance of results from circulating tumor DNA and tissue‐based RAS testing. Issue 2 (20th January 2017) - Schmiegel, Wolff; Scott, Rodney J.; Dooley, Susan; Lewis, Wendy; Meldrum, Cliff J.; Pockney, Peter; Draganic, Brian; Smith, Steve; Hewitt, Chelsee; Philimore, Hazel; Lucas, Amanda; Shi, Elva; et al.
Abstract : An accurate blood‐based RAS mutation assay to determine eligibility of metastatic colorectal cancer (mCRC) patients for anti‐EGFR therapy would benefit clinical practice by better informing decisions to administer treatment independent of tissue availability. The objective of this study was to determine the level of concordance between plasma and tissue RAS mutation status in patients with mCRC to gauge whether blood‐based RAS mutation testing is a viable alternative to standard‐of‐care RAS tumor testing. RAS testing was performed on plasma samples from newly diagnosed metastatic patients, or from recurrent mCRC patients using the highly sensitive digital PCR technology, BEAMing (beads, emulsions, amplification, and magnetics), and compared with DNA sequencing data of respective FFPE (formalin‐fixed paraffin‐embedded) tumor samples. Discordant tissue RAS results were re‐examined by BEAMing, if possible. The prevalence of RAS mutations detected in plasma (51%) vs. tumor (53%) was similar, in accord with the known prevalence of RAS mutations observed in mCRC patient populations. The positive agreement between plasma and tumor RAS results was 90.4% (47/52), the negative agreement was 93.5% (43/46), and the overall agreement (concordance) was 91.8% (90/98). The high concordance of plasma and tissue results demonstrates that blood‐based RAS mutation testing is a viable alternative to tissue‐based RAS testing. Abstract : Implementation of circulating tumor DNA testing in clinical practice has been hindered by the variable performance of available methods. Here, we demonstrate that plasma mutation testing using BEAMing as a standardized platform is comparable to tumor tissue testing and can be useful in the clinic to select patients with metastatic colorectal cancer for targeted therapy.